Escola é lugar de… educação como prevenção de violência de gênero em São Leopoldo/RS - Koenig, Gabriela Dávila (Universidade do Vale do Rio dos Sinos, 2023)
This dissertation investigates gender relations within educational settings, with the aim of exploring education's potential as a tool to prevent gender-based violence. Consequently, it delves into an examination of gender constructs through educational processes and their evolution. The initial focus centers on an exploration of the norms that guide national, municipal, and local education systems. Subsequently, the study delves into school practices, assessing their potential contributions, or lack thereof, to the role of education in preventing gender violence. To accomplish this objective, the research employs an ethnographic study of a school environment, utilizing participant observation methods inspired by Eckert and Rocha (2008). The investigation is centered around the Municipal Elementary School Francisco Cândido Xavier, located in São Leopoldo/RS, during the period from 06/03/2022 to 05/05/2023. In conjunction with this approach, an analysis of relevant documents, including the National Education Plan (2014-2024), the Municipal Education Plan (2014-2024), and the School Regulations (2019), is conducted. In the analysis of gender, the framework proposed by Joan Scott (1985) and Raewyn Connell (2016) is employed. This framework shines a spotlight on the power dynamics inherent in and shaping gender relations through societal conflicts and interactive dynamics. The exploration of gender practices within the realm of education is informed by Guacira Lopes Louro's perspective (1997), which emphasizes the interconnection and mutual construction of both systems. Further enriching this perspective, the philosophies of bell hooks (2017) are introduced to the discourse, advocating for a popular education grounded in autonomy, freedom, and participatory learning. Additionally, anthropological insights into education, as viewed through the lens of Sandra Tosta (2020), are integrated, drawing parallels between education and culture. By engaging with these diverse perspectives, the dissertation aims to shed light on the intricate interplay between education, gender, power, and cultural dynamics within the context of preventing gender violence.
Keywords: Educação; Violência de gênero; Direitos humanos; Cidadania; Education; Gender violence; Human rights; Citizenship; ACCNPQ::Ciências Humanas::Sociologia